CFD and experimental study of heat dissipation from an anti-coning, pin vented, inboard mounted brake disc - Mingozzi, Filippo; Verdin, Patrick G.; Gucci, Lorenzo; Tirovic, Marko (Sage, 2022)
Anti-coning brake discs are known for their superior NVH characteristics when compared to other disc designs, but also for poorer heat dissipation. Cooling characteristics of such a disc design are studied numerically and experimentally on a specially developed Thermal Spin Rig. The disc is installed inboard on a high-performance off-road vehicle, with portal axles and wheel drives, resulting in nearly fourfold higher disc rotational speeds in comparison to the wheel speeds. Being exposed to the free-flowing air and rotating much faster makes this application well worth the attention and deeper study in terms of disc cooling. Computational Fluid Dynamics (CFD) analyses show a detailed distribution of air velocities and pathlines, temperatures, pressures, and convective heat transfer coefficients. The results are all very coherent, conveying very useful information, both qualitatively and quantitatively. Their cumulative effect has been successfully validated by comparing the CFD predicted average convective heat transfer coefficients (hconv) with the experimental results obtained on the Thermal Spin Rig, in a controlled environment. CFD results show to be very close to average hconv values calculated from measured cooling curves. The agreement is very good for the wide temperature and speed range. The overall relative differences are under 5%, and in most cases under 3%, except for the low disc rotation speeds, which show a maximum relative difference of 12.5% calculated at 200 rpm, for the disc heated to 300◦ C. Such outcomes give confidence in the CFD results for future work in both disc design and vehicle installations.
Keywords: Heat transfer; Computational Fluid Dynamics; ANSYS CFX; Brake disc; Thermal analysis